Monitoring, Evaluation, and Analysis of BPJS Referral Implementation at Primary Healthcare Facilities: Literature Review - Norman, Fadhilah; Palloge, Salahuddin Andi; Syamsu, Rachmat Faisal (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Social Security Administering Body (BPJS) is a social institution in Indonesia that organizes social security programs. The National Health Insurance Program (JKN) aims to improve community welfare through a capitation financing system at First Level Health Facilities (FKTP). The high number of referrals suggests that the referral system at Puskesmas has not been properly implemented, highlighting the need for monitoring and evaluation. This study aims to assess the implementation of BPJS referrals at FKTP. A literature review was conducted using Google Scholar to find relevant articles published from 2020 to 2024, resulting in the collection of seven journals. Findings indicate that while monitoring and evaluation of BPJS referrals are ongoing, implementation is not optimal and faces challenges.